Pesantren Sebagai Lembaga Intermediasi Agribisnis: Peran Ganda Penghubung Permodalan, Penjamin Offtaker, dan Pendamping Dalam Keberlanjutan Usaha Ternak Domba Mitra - Azhar, Alif Lamro Al; Warnaen, Andi; Purbarani, Saraswati Ayu (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Research on livestock farmer empowerment generally focuses on financing or mentoring aspects separately, while studies explaining the role of Islamic boarding schools (pesantren) as institutions that integrate capital, marketing, and mentoring functions are still limited. This study aims to analyze the role of the Insan Kamil Islamic Boarding School in empowering sheep farmers through the Dombastis Program in Nganjuk Regency. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using thematic analysis assisted by NVivo 12. The results show that Islamic boarding schools perform three integrated roles: as intermediaries that facilitate access to sharia financing without physical collateral, offtakers that guarantee the absorption of livestock products, thereby reducing livestock farmers' dependence on middlemen, and mentors who provide technical guidance and spiritual strengthening. The integration of these three roles has proven capable of simultaneously overcoming obstacles in access to capital, marketing, and managerial capacity of livestock farmers. These findings expand the study of Islamic boarding school-based economic empowerment by showing that Islamic boarding schools function not only as religious educational institutions but also as socio-economic institutions that build a sustainable ecosystem for empowering smallholder farmers.